2012
DOI: 10.1007/s00249-012-0860-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of heme complexed with human serum albumin: a theoretical approach

Abstract: Human serum albumin (HSA) is the most abundant protein in the blood serum. It binds several ligands and has an especially strong affinity for heme, hence becoming a natural candidate for oxygen transport. In order to analyze the interaction of HSA-heme, molecular dynamics simulations of HSA with bound heme were performed. Based on the results of X-ray diffraction, the binding site of the heme, localized in subdomain IB, was considered. We analyzed the fluctuations and their correlations along trajectories to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…During the simulated time of 100 ns, the RMSD value of HSA and trans -resveratrol complex was lesser than the RMSD value of HSA alone, this also suggests the stability of the HSA system after binding with trans -resveratrol molecule. The RMSD values of HSA obtained in the present study are in good agreement with the previously reported studies 55 .
Figure 13 MD simulation analysis of HSA and trans- resveratrol binding interaction showing (a) RMSD plot for 100 ns simulation, (b) RMSF plot showing the fluctuations of the residues in HSA and HSA-T-res complex.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…During the simulated time of 100 ns, the RMSD value of HSA and trans -resveratrol complex was lesser than the RMSD value of HSA alone, this also suggests the stability of the HSA system after binding with trans -resveratrol molecule. The RMSD values of HSA obtained in the present study are in good agreement with the previously reported studies 55 .
Figure 13 MD simulation analysis of HSA and trans- resveratrol binding interaction showing (a) RMSD plot for 100 ns simulation, (b) RMSF plot showing the fluctuations of the residues in HSA and HSA-T-res complex.
…”
Section: Resultssupporting
confidence: 93%
“…After that, it decreases continuously up to 90 ns, and after that, it remains constant up to 100 ns. The R g values of HSA obtained are in accordance with the previously reported studies 55 , 57 . On the other hand, the R g value of HSA- trans -resveratrol complex initially decreases from 0 to 20 ns.…”
Section: Resultssupporting
confidence: 92%
“…The Root Mean Square Fluctuation of the Cα backbone was computed for the Unliganded HSA and HSA-4-PBA complex from b-factors (RMSF = √3B/(8π 2 )), where B is the b-factor. The RMSF profiles of HSA show high fluctuations in the C-terminal domain (IIIB) as compared to the N-terminal (IA) ( Fig 6A ); this is in agreement with earlier studies [ 31 ]. Much of the HSA fluctuations are observed in the Sub domain IA and IIIB of all FA binding sites ( Fig 6A ).…”
Section: Resultssupporting
confidence: 92%
“…Among the top ten eigen values, the first two accounted largely for protein motion in each complex ( Fig 6C ). Long chain fatty acids binds linearly to the FA2 and FA5 sites (due to their large binding cavities), and nonlinearly at FA 1, 3 and 6 due to internal strain (owing to smaller cavity space) [ 31 ]. Whereas, the 4-PBA carbon chain being very small, facilitates stable interaction at much smaller cavities localized at FA1, 3, 4 and 6 causing less protein motion.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the HSA-ligand structures obtained using docking and MD simulations have been applied to quantum mechanics calculations of the excitation energies [138] and quantitative structure-activity relationship analyses of HSA-ligand binding affinity [139]. In addition, longer time scale (≥100 ns) MD simulations have been recently performed for analyses of the HSA-aspirin complex [140], the HSA-heme complex [141], the structural role of disulfide bridges in HSA [142], and the conformational flexibility of the unliganded HSA [119]. Thus, MD simulations are playing an increasingly important role in structural-functional studies of HSA.…”
Section: Simulations For Analyzing Conformations Of Hsa or Hsa-ligmentioning
confidence: 99%